Aerobic and anaerobic correlates of multiple sprint cycling performance - Glaister, M.; Stone, M. H.; Stewart, A. M.; Hughes, M. G.; Moir, G. L. (The Journal of Strength and Conditioning Research, 2006)
The aims of this study were to examine (a) the relationship between maximal oxygen uptake (VO2max) and several performance indices of multiple sprint cycling; (b) the relationship between maximal accumulated oxygen deficit (MAOD) and those same performance indices; and (c) the influence of recovery duration on the magnitude of those relationships. Twenty-five physically active men completed a VO2max test, a MAOD test, and 2 maximal intermittent (20 x 5 seconds) sprint cycling tests with contrasting recovery periods (10 seconds or 30 seconds). Mean +/- SD for age, height, and body mass were 20.6 +/- 1.5 years, 177.2 +/- 5.4 cm, and 78.2 +/- 8.2 kg, respectively. All tests were conducted on a friction-braked cycle ergometer with subsequent data normalized for body mass. Moderate (0.3 <= r < 0.5) positive correlations were observed between power output data and MAOD (range, 0.31-0.46; 95% confidence limits, -0.10 to 0.72). Moderate to large positive correlations also were observed between power output data and VO2max, the magnitude of which increased as values were averaged across all sprints (range, 0.45-0.67; 95% confidence limits 0.07-0.84). Correlations between fatigue and VO2max were greater in the intermittent protocol with 30-second recovery periods (r = -0.34; 95% confidence limits, 0.06 to -0.65). The results of this study reflect the complex energetics associated with multiple sprint work. Though the findings add support to the idea that multiple sprint sports demand a combination of speed and endurance, further longitudinal research is required to confirm the relative importance of these parameters.